Health Care Resource Utilization Associated With Parkinson Disease Among Medicare Beneficiaries. (10th August 2021) - Gandhi, Aakash Bipin; Onukwugha, Eberechukwu; Albarmawi, Husam; Johnson, Abree; Myers, Daniela E.; Gray, David; Alvir, Jose; Hynicka, Lauren; Shulman, Lisa M.
Abstract : Objective: To compare differences in health care resource utilization (HcRU) over time between Medicare beneficiaries with and without Parkinson disease (PD). Methods: This retrospective observational study used the Chronic Conditions Data Warehouse (5% Medicare sample) between 2005 and 2015. In a propensity score–matched (age, sex, race, and comorbidity adjusted) sample of beneficiaries with and without PD, we examined all-cause HcRU due to inpatient admissions, emergency department (ED) admissions, skilled nursing facility (SNF) admissions, health care provider encounters, neurologist visits, rehabilitation service visits, and non-PD medication fills. Relative to beneficiaries without PD, we reported adjusted incidence rate ratios (IRRs) and 95% confidence intervals (CIs) for beneficiaries with PD using generalized linear models with log link and negative binomial variance functions. Results: A total of 467, 064 Medicare enrollees (unmatched sample) met the inclusion criteria. Of these, 3.3% had PD. In the matched sample and relative to beneficiaries without PD, beneficiaries with PD displayed higher rates of inpatient admissions (IRR 1.29, 95% CI 1.24–1.34), ED admissions (IRR 1.31, 95% CI 1.27–1.34), SNF admissions (IRR 2.00, 95% CI 1.92–2.09), health care provider encounters (IRR 1.18, 95% CI 1.16–1.20), neurologist visits (IRR 5.57, 95% CI 5.35–5.78), rehabilitation service visits (IRR 1.47, 95% CI 1.41–1.53), and non-PD medication fills (IRR 1.10, 95% CI 1.08–1.11) over time. Conclusion: These results reflect patterns of medical care among Medicare beneficiaries with PD. The findings can help clinicians, payers, and policy makers make evidence-based decisions for the allocation of scarce health care resources for PD management. Classification of Evidence: This study provides Class II evidence that Medicare beneficiaries with PD use more health care resources than matched controls without PD.